2021
DOI: 10.1186/s12920-021-01053-3
|View full text |Cite|
|
Sign up to set email alerts
|

Compound heterozygous variants including a novel copy number variation in a child with atypical ataxia-telangiectasia: a case report

Abstract: Background Ataxia-telangiectasia is a rare autosomal recessive, neurodegenerative disorder caused by alterations in the ATM gene. The majority of ATM pathogenic variants are frameshift or nonsense variants which are predicted to truncate the whole ATM protein. Herein, we report on an ataxia telangiectasia child with atypical phenotype who was identified as compound heterozygous for two ATM variants involving a previously described pathogenic single nucleotide variation (SNV) and a novel copy nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Of the 18246 cases, family history of A-T was reported in 1274 cases ( Table 2 ) and 142 cases (53 studies) had 199 illnesses or symptoms other than A-T in a relative ( Fig 3A ). 1279 cases (109 studies [ 15 , 53 , 65 , 71 , 72 , 78 , 87 , 88 , 95 , 99 – 101 , 109 , 110 , 115 , 118 221 ]) were the children of consanguineous relationships, and 186 cases (86 studies [ 23 , 33 , 41 , 50 , 54 , 62 , 63 , 65 , 71 , 74 , 84 , 88 , 95 , 111 , 116 , 142 , 146 , 151 – 153 , 188 , 208 – 210 , 212 , 214 , 216 , 218 , 219 , 221 277 ]) were reported as being born of non-consanguineous relationships.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 18246 cases, family history of A-T was reported in 1274 cases ( Table 2 ) and 142 cases (53 studies) had 199 illnesses or symptoms other than A-T in a relative ( Fig 3A ). 1279 cases (109 studies [ 15 , 53 , 65 , 71 , 72 , 78 , 87 , 88 , 95 , 99 – 101 , 109 , 110 , 115 , 118 221 ]) were the children of consanguineous relationships, and 186 cases (86 studies [ 23 , 33 , 41 , 50 , 54 , 62 , 63 , 65 , 71 , 74 , 84 , 88 , 95 , 111 , 116 , 142 , 146 , 151 – 153 , 188 , 208 – 210 , 212 , 214 , 216 , 218 , 219 , 221 277 ]) were reported as being born of non-consanguineous relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest gestation was reported as “< 30 weeks”. Birth weight was reported in 41 cases (34 studies [ 43 , 59 , 63 , 84 , 108 , 110 , 111 , 139 , 178 , 206 , 212 , 231 , 242 , 252 , 254 , 263 , 268 , 272 , 276 , 298 , 305 , 325 , 372 , 380 , 384 , 391 , 399 – 406 ]) with median (range) of 2.9.5 (1.32 to 4.08) kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The matched transcript profile might be associated with the atypical manifestation of A-T phenotype. Lee et al reported an atypical A-T harbouring compound heterozygous variant in A-T manifested with normal serum AFP, mild atrophy, delayed development and oculomotor apraxia 60 . These reports indicate that hypomorphic mutations are indeed associated with attenuated A-T phenotype 8 , 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…This error may have affected the interpretation of the results, and therefore, the figure was replaced with the earlier correct version. The original article [ 1 ] has been corrected.…”
Section: Correction To: Bmc Med Genomics 14 204 (2021) 101186/s12920-021-01053-3mentioning
confidence: 99%